2018
DOI: 10.4067/s0370-41062018000200196
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de vida relacionada con la salud en pacientes pediátricos con enfermedad inflamatoria intestinal

Abstract: Recibido el 30 de marzo de 2017; aceptado el 29 de noviembre de 2017Palabras clave: Calidad de vida relacionada con la salud; enfermedad inflamatoria intestinal; niños; colitis ulcerosa ResumenIntroducción: La Enfermedad Inflamatoria Intestinal (EII) es un grupo de patologías crónicas que tiene implicancias en diversos factores que afectan la calidad de vida en el paciente pediátrico. Objetivos: Describir la calidad de vida relacionada con la salud (CVRS) en pacientes pediátricos con Enfermedad Inflamatoria In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…The results of a number of observational studies involving adult patients with IBD devoted to the study of disease outcomes indicate that the young age of the disease onset is associated with an increased risk of adverse outcomes, which confirms the importance of early treatment initiation in children, as well as the need for doctors to consider such an aspect as quality of life (QOL) of this category of patients [6][7][8].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The results of a number of observational studies involving adult patients with IBD devoted to the study of disease outcomes indicate that the young age of the disease onset is associated with an increased risk of adverse outcomes, which confirms the importance of early treatment initiation in children, as well as the need for doctors to consider such an aspect as quality of life (QOL) of this category of patients [6][7][8].…”
mentioning
confidence: 87%
“…A number of studies have been performed on the assessment of QOL of patients with IBD, and, according to their results, in most patients, including those with UC, its level is statistically significantly lower compared to the corresponding characteristics in the general population [9][10][11]. It was shown that children and adolescents with IBD, including UC, are physically less developed and active compared to healthy peers [7,8], they are characterized by disturbances in family relationships [6,11], limited participation in social activities, disorders of the emotional spectrum, learning problems, more frequent missed classes [7].…”
mentioning
confidence: 99%
“…Este hallazgo concuerda con los datos del estudio español de López y colaboradores (10) . Cabe resaltar que estos datos no pudieron ser reproducidos en un estudio llevado a cabo en Chile en población pediátrica (11) ; posiblemente debido al tamaño de la muestra.…”
Section: Variablesunclassified
“…Ademais, as manifestações clínicas multissistêmicas e a alta prevalência de complicações, acarretam maiores taxas de hospitalização, culminando em absenteísmo escolar e implicações para autoestima e imagem social dos pacientes (SNYDER et al, 2021). Além disso, há dificuldade na manutenção do tratamento, visto que as drogas utilizadas possuem amplo espectro de efeitos colaterais e há baixa adesão às modificações dietéticas complexas e excludentes para o manejo da DC e, quando aderidas, apresentam impacto na qualidade de vida, uma vez que interferem no estilo de vida do paciente (SILVEIRA et al, 2008;LOURENÇO et al, 2016;OJEDA et al, 2018;SUSKIND et al, 2020).…”
Section: Introductionunclassified